EXPLORING THE CORRELATION BETWEEN EDUCATION AND INCOME: THE IMPACT OF EDUCATION ON PERSONS WITH DISABILITIES IN THE FORMAL SECTOR - Putri Meliza Sari; Nasri Bachtiar; Werry Darta Taifur (Transpublika Publisher, 2023)
Education is the key gateway for people with disabilities to become skilled laborers for self-reliance and to create better welfare. Using Sakernas data for 2021, this study aims to analyze the impact of education level on people with disabilities between two groups, namely people with disabilities with high education and people with low education, with additional observations on people with disabilities working in the formal or informal sector. The sample selected for the study is made up of workers with disabilities who have an income of 27,049. The higher education category is the level of education completed by persons with disabilities at the equivalent of high school to doctoral level, while the low education group is the level of education of persons with disabilities at the junior high school level and below. The results of the Propensity Score Matching (PSM) method state that higher education and working in the formal sector have an impact of more than 58 percent on increasing their income compared to persons with disabilities who have low education and work in the informal sector.